Quantification of [18F]DPA-714 Binding in the Human Brain: Initial Studies in Healthy Controls and Alzheimer'S Disease Patients. Issue 5 (May 2015) - Golla, Sandeep SV; Boellaard, Ronald; Oikonen, Vesa; Hoffmann, Anja; van Berckel, Bart NM; Windhorst, Albert D; Virta, Jere; Haaparanta-Solin, Merja; Luoto, Pauliina; Savisto, Nina; Solin, Olof; Valencia, Ray; et al.
Fluorine-18 labelled N, N -diethyl-2-(2-[4-(2-fluoroethoxy)phenyl]-5, 7-dimethylpyrazolo[1, 5-α]pyrimidine-3-yl)acetamide ([ 18 F] DPA-714) binds to the 18-kDa translocator protein (TSPO) with high affinity. The aim of this initial methodological study was to develop a plasma input tracer kinetic model for quantification of [ 18 F]DPA-714 binding in healthy subjects and Alzheimer's disease (AD) patients, and to provide a preliminary assessment whether there is a disease-related signal. Ten AD patients and six healthy subjects underwent a dynamic positron emission tomography (PET) study along with arterial sampling and a scan protocol of 150 minutes after administration of 250 ± 10 MBq [ 18 F]DPA-714. The model that provided the best fits to tissue time activity curves (TACs) was selected based on Akaike Information Criterion and F-test. The reversible two tissue compartment plasma input model with blood volume parameter was the preferred model for quantification of [ 18 F]DPA-714 kinetics, irrespective of scan duration, volume of interest, and underlying volume of distribution ( V T ). Simplified reference tissue model (SRTM)-derived binding potential (BPND ) using cerebellar gray matter as reference tissue correlated well with plasma input-based distribution volume ratio (DVR). These data suggest that [ 18 F]DPA-714 cannot be used for separating individual AD patients from heathy subjects, but further studies including TSPO binding status are needed to substantiate these findings.